More Alike than Different: Student Perceptions of Academic Librarians by Genders and Subject Areas. Issue 3 (2nd October 2021) - Price, Elizabeth; Fagan, Jody Condit
ABSTRACT: This study explored differences in how undergraduate students of different genders and academic disciplines perceived academic librarians at a U.S. public university. No evidence indicated differences between students identifying as male or female, and few statistically significant differences were found among four Subject Areas (Arts, Humanities + Social Sciences, Business, Health + Education, and STEM). Our results have implications for local practice though they are not generalizable to other institutions. Despite a lack of significant findings, librarians should continue to explore ways to measure how students of different disciplines perceive academic libraries and/or librarians as valuable to their academic success.